Cognitive ability and in-group bias: An experimental study - Paetzel, Fabian; Sausgruber, Rupert (Journal of public economics, 2018)
We study the role of performance differences in a task requiring cognitive effort on in-group bias. We show that the in-group bias is strong in groups consisting of high-performing members, and it is weak in low-performing groups. This holds although high-performing subjects exhibit no in-group bias as members of minimal groups, whereas low-performing subjects strongly do. We also observe instances of low-performing subjects punishing the in-group favoritism of low-performing peers. The same does not occur in high-performing or minimal groups where subjects generally accept that decisions are in-group biased. •Performance differences in a task requiring cognitive ability affect in-group bias.•In-group bias is strong in groups consisting of high-performing members.•High-performing subjects exhibit no in-group bias as members of minimal groups.•Low-performing subjects punish the in-group favoritism of low-performing peers.•Results are consistent with entitlement considerations between groups.